2012
DOI: 10.1007/s10578-012-0329-7
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ and Fathers’ Ratings of Family Relationship Quality: Associations with Preadolescent and Adolescent Anxiety and Depressive Symptoms in a Clinical Sample

Abstract: This study examined the independent associations among three family relationship quality factors--cohesion, expressiveness, and conflict--with youth self-reported depressive and anxiety symptoms in a clinical sample of anxious and depressed youth. Ratings of family relationship quality were obtained through both mother and father report. The sample included families of 147 preadolescents and adolescents (56.6 % female; 89.8 % Caucasian), 11-18 years old (M = 13.64, SD = 1.98) assigned a principal diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 52 publications
3
19
0
Order By: Relevance
“…In our study family dynamics were significantly correlated with depressive symptoms, concurring with findings from Queen et al [31] The family dynamics of cohesion, support and communication appear to coincide with the adolescent-parent attachment dynamic. More of these dynamics within the family is related to a greater degree of attachment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study family dynamics were significantly correlated with depressive symptoms, concurring with findings from Queen et al [31] The family dynamics of cohesion, support and communication appear to coincide with the adolescent-parent attachment dynamic. More of these dynamics within the family is related to a greater degree of attachment.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, a longitudinal study conducted by Sze et al [30] showed that close and caring families, reflective of high levels of family cohesion, communication and support, are associated with lower levels of depressive symptomatology in adolescence. Queen et al [31] investigated mothers' and fathers' reports of family cohesion on depressive symptoms reported by adolescents. Their findings indicated a strong correlation between family cohesion and depressive symptoms in their adolescent sample.…”
Section: Family Functioning Adolescent Attachment and Adolescent Depmentioning
confidence: 99%
“…For example, family cohesion has found to be predictive of fewer depressive symptoms for adolescent boys (Queen, Stewart, Ehrenreich-May, & Pincus, 2013) and feelings of loneliness for adolescent girls (Johnson, LaVoie, & Mahoney, 2001). These findings have also been confirmed in early adolescents, with low levels of cohesion related to higher internalizing problems (Deng et al, 2006).…”
Section: Family Cohesionmentioning
confidence: 99%
“…Similarly, military youth may also be more at-risk for anxiety, especially during military transitional periods, such as deployment or relocation (Huebner and Mancini 2005). Adolescent anxiety often co-occurs with other internalizing and externalizing symptoms, such as depression (Johnson and Greenberg 2013;Queen et al 2013) and emotion dysregulation (Bender et al 2012). Additionally, adolescent anxiety places youth at increased risk for anxiety in adulthood (Duchesne et al 2008).…”
Section: Introductionmentioning
confidence: 99%